Determination of suitable configuration parameters for linear feedback shift register using binary bat optimization algorithm - Eröz, Eyüp; Tanyıldızı, Erkan; Özkaynak, Fatih (My University, 2021)
Abstract— It is a difficult problem in the field of computer science to be able to answer the question of what configuration parameters will be used to generate long bit strings with linear feedback shift register structures, which is a component widely used in many practical applications that require random behavior. Since this difficult challenge is a problem with NP computational complexity, the difficulty of developing solutions in classical ways has been tried to be solved by using optimization algorithms. In this study, all possible configurations that can be used for all linear feedback shift register structures up to eight degrees have been determined using the binary bat optimization algorithm. Statistical properties of random sequences generated using these configurations have been tested using the chi-square test. All the resulting configurations are shared as a public dataset. It is thought that these successful results can be used effectively in various practical applications by many researchers in the future
Bildiri - Yayımlanmış
Keywords: Randomness; Lfsr; Binary bat optimization